Estimation of hydraulic conductivity in shallow unconfined aquifers using concrete-lined large-diameter hand-dug wells - Ibrahim, Kehinde Olojoku (University of the Free State, 2019)
Large-diameter hand-dug wells are the main source of water supply for drinking, domestic and irrigation uses in many rural areas of sub-Saharan African countries and other developing countries of the world. In many rural areas of developing sub-Saharan African countries, the use of unscreened lining is the most common method of protecting large-diameter hand-dug wells against collapsing and pollution due to the simplicity and affordability of the method. This method prevents horizontal water flow to the well and water flow to the well through the well base, which makes the existing methods inapplicable for estimating hydraulic conductivity in screened hand-dug wells. The method developed involved to derive horizontal hydraulic conductivity (K) from apparent hydraulic conductivity (Ka). To demonstrate the viability of the developed method, field recovery tests were conducted in twelve (12) unscreened concrete-lined and screened lined large-diameter hand-dug wells based on the accessibility of the wells at test site to estimate apparent hydraulic conductivity (Ka) and horizontal hydraulic conductivity (K). The geophysical study of the test site was aimed to estimate the aquifer type, depth to water table and identification of strata and vadose zone thickness. The hydrogeochemical studies involved the collection and analysis of water samples from twenty (20) large-diameter hand-dug wells at the test site during rainy and dry seasons and was aimed at monitoring the groundwater quality and groundwater type of the test site. The results showed that the estimated apparent hydraulic conductivity Ka were lower than the horizontal hydraulic conductivity K, which indicated the effect of the unscreened concretelining. A relationship between Ka and K was established to make a correction factor for estimation of K from Ka by a regression analysis which showed a significant strong relationship of 0.00 between Ka and K using a bivariate Pearson correlation coefficient. This study has formulated a method that can be used to estimate aquifer hydraulic conductivity in unscreened concrete-lined large-diameter hand-dug wells. This will help to estimate the yield potential of the wells and evaluate the amount of water that can be abstracted or pumped from the wells in the rural areas of the developing world where unscreened concrete-lined largediameter hand-dug wells are being used. Further studies are recommended to quantify the amount of energy loss in flow as a result of non-horizontal water flow into the well.
Thesis (Ph.D.(Geohydrology))--University of the Free State, 2019
Keywords: Apparent hydraulic conductivity; Horizontal hydraulic conductivity; Large-diameter hand-dug wells; Rural areas; Screened lining of wells; Unscreened lining of wells; Linings of wells; Africa, Sub-Saharan - Rural conditions